Wood productivity of Prosopis flexuosa D.C. woodlands in the central Monte: Influence of population structure and tree-growth habit - Alvarez, Juan Agustin (2011)
A balance between forest production and protection is hard to achieve in arid zones due to their low potential for wood production. Prosopis flexuosa woodlands are the major woody formations in the Monte desert and are currently in a degraded state due to intense use. The main degradation factors in the study area are overgrazing and firewood extraction. We developed allometric models to estimate the aerial biomass of P. flexuosa, compared annual growth rates of one- and multi-stemmed individuals through dendrochronological methods, and estimated the productivity of four structurally different woodlands in the central Monte. Total dry weight was best estimated by power equations. Annual increments in basal area and dry weight were initially larger for multi- than one-stemmed individuals. However, whereas multi-stemmed individuals rapidly decreased their growth rates after 60 years of age, one-stemmed trees maintained steady growth rates during the first 100 years. Depending on woodland density and tree size, total woodland biomass varied between 4000 and 15 000 kg ha-1. Wood productivity was similar in all four woodlands studied (121.6-173.7 kg ha-1 year-1). Our results reveal the importance of tree growth habit to productivity, and suggest that regulated extraction of firewood and poles from old multi-stemmed individuals could optimize wood productivity and contribute to the sustainable use and conservation of these woodlands.